USAHA PEMBINAAN PENGEMBANGAN PROFESI GURU DAN IMPLIKASINYA TERHADAP MUTU PENDIDIKAN DI MTS TARBIYAH ISLAMIAH KABUPATEN TANAH DATAR - Zilviana Zilviana (IAIN Batusangkar, 2016)
The purpose of this research was to know the implementation of teachers’ professional development in Islamic Secondary School Tarbiyah Islamiah Tanah Datar and the impact of the implementation of the teachers’ professional development to the quality of education in Islamic Secondary School Tarbiyah Islamiah Tanah Datar. This research was qualitative case study. The result obtained indicate that particularly in Islamic Secondary School Tarbiyah Islamiah Pariangan, Islamic Secondary School Tarbiyah Islamiah Tanjung Barulak and Islamic Secondary School Tarbiyah Islamiah Jaho were not good, the coaching responsibilities of teachers’ professional development is still left to the headmaster and the participation of regional government was less. Keywords: Teachers’ Professional Development, Islamic Secondary School, Tarbiyah Islamiah, Quality of Education, Tanah Datar.